2004
DOI: 10.1111/j.1538-7836.2004.00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of recombinant W501S mutated human γ-glutamyl carboxylase

Abstract: Summary. A mutation (W501S) in the vitamin K-dependent c-glutamyl carboxylase (VKC) that leads to a congenital bleeding disorder was recently discovered in two patients. To characterize the enzyme defect, recombinant VKC-W501S was expressed in and purified from insect cells. The major effect of the mutation appears to be to decrease the affinity of the carboxylase for the propeptide of its substrates. This observation agrees with recent data that place part of the propeptide binding site within residues 495-51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…One of these mutations, Trp501Ser, is located in the proximity of Arg485Pro [9]. By expression studies, Soute et al [13] demonstrated that Trp501Ser decreased the affinity of the g-carboxylase for the propeptide of its substrates, thus supporting our assumption that the Arg485Pro mutation is interfering with propeptide binding.…”
Section: Discussionsupporting
confidence: 50%
“…One of these mutations, Trp501Ser, is located in the proximity of Arg485Pro [9]. By expression studies, Soute et al [13] demonstrated that Trp501Ser decreased the affinity of the g-carboxylase for the propeptide of its substrates, thus supporting our assumption that the Arg485Pro mutation is interfering with propeptide binding.…”
Section: Discussionsupporting
confidence: 50%
“…[9][10][11][12] Those patients had mutations (Leu394Arg and Trp501Ser) that were subsequently shown to decrease VKD substrate binding. 30,31 Because VKD substrate binding regulates carboxylase affinity for vitamin K, 22 this decrease impaired vitamin K binding (ie, causing an increase in K m for vitamin K), which can explain why these patients responded to vitamin K supplementation. The lack of response of the proposita, then, suggests that the Trp157Arg mutation impairs vitamin K catalysis rather than binding.…”
Section: Discussionmentioning
confidence: 99%
“…13,28 Mutations associated with hereditary combined VKD coagulation factor deficiency are rare. The carboxylase is encoded by a single gene, 29 and only 3 naturally occurring missense mutations have previously been identified: Leu394Arg, 10 which is impaired in both Glu binding and propeptide binding, 30 Trp501Ser, 9,11 which shows decreased propeptide binding, 31 and Arg485Pro, 12 whose functional analysis has not yet been reported. In all 3 cases, vitamin K supplementation resulted in at least partial restoration of VKD factor function, consistent with the effect of VKD protein binding on carboxylase affinity for vitamin K. Two carboxylase gene mutations in noncoding regions are also known that include a splice site mutation in intron 2 12 and a short deletion affecting a putative cis-acting element in the promoter of the gene.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with the W501S mutation have high levels of undercarboxylated osteocalcin, 4 which is suspected to be deleterious to bone health. Developmental skeletal defects associated with inappropriate calcium deposition, such as those seen in the well-known warfarin embryopathy, have been reported in an infant with a putative VKOR mutatation, 5 but these compound heterozygous mutations of ␥-carboxylase appear to be the first to be associated with skeletal abnormalities as well as other severe pathologic features.…”
Section: ␥-Glutamyl Carboxylation: Squaring the Vitamin K Cycle -----mentioning
confidence: 99%
“…The higher vitamin K requirement seen in the L394R and W501S mutations seems to arise from the defective binding of glutamate and propeptide substrates, respectively, which has the knock-on effect of reducing the affinity for the KH 2 cofactor compared with the wild-type enzyme. 4 Darghouth and colleagues make the intriguing suggestions that the highly conserved W157 residue is part of a hydrophobic vitamin K binding site, and that the W157R mutation impairs vitamin K catalysis rather than binding.The possible consequences of mutational defects in the vitamin K cycle extend beyond the coagulation function of VKD proteins. Patients with the W501S mutation have high levels of undercarboxylated osteocalcin, 4 which is suspected to be deleterious to bone health.…”
mentioning
confidence: 99%